Stuck between two worlds: Karamanlidika literary production, Evangelinos Misailidis and Temaşa-i Dünya ve Cefakâr u Cefakeş as a case of rewriting - Şişmanoğlu Şimşek, Şehnaz. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
This dissertation aims to situate in modern Turkish literature a narrative fiction, previously overlooked by Turkish literary historians, called Temaşa-i Dünya ve Cefakâr u Cefakeş (1871-1872) by Evangelinos Misailidis (1820-1890), an Ottoman Christian-Orthodox citizen. The dissertation is built on three objectives: First of all, Karamanlidika literature is foregrounded as one of the significant aspects forming the plurality of nineteenth century Ottoman literature. Secondly, Karamanlidika literature is analysed in terms of its processes of production and multidimensional relations of dominance with contemporary Ottoman-Muslim-Turkish and Greek literatures analysing Temaşa-i Dünya as a case study. The third objective is to criticise the argument that Temaşa-i Dünya is just an imitation of the Greek novel O Polipathis (1839). Using mainly Gérard Genette’s theoretical framework and narratological concepts, it can be said that Misailidis has significantly transformed Polipathis semantically and literarily, by changing the style and the language of the narrative, adding different characters, stories and contexts as well as traditional folklore forms having muslim and non-muslim origins. Hence, this study also focuses on the problem of the rewriting of a text using varied writing strategies. The major factor determining the content, literary features and the genre of Temaşa-i Dünya is “liminality”; described as “being in a threshold state ‘betwixt and between’ existing orders.” A member of the Turcophone Anatolian Orthodox community, often treated as being an anomaly by the Grecophone Greek authorities from the second half of the nineteenth century onwards, Misailidis, stuck between Ottoman/Greek, Muslim and Anatolian identities, created a narrative which is “liminal” in various aspects. The text moves between the ideology of the Greek Enlightenment, the social and linguistic Ottoman-Greek and Ottoman-Muslim traditions and the Christian Orthodox religion. Finally, this dissertation claims that, as it contains a diversity of genres and speech as well as new narrative possibilities, Temaşa-i Dünya is an original novel that reveals the multicultural Ottoman world and Ottoman literature in the nineteenth century.